Heterogeneous Cloud Radio Access Network - Singh, P; Singh, N; Rani, S (International Journal of Computer Sciences and Engineering, 2025)
To reduce the several in between base station processing in heterogeneous network we connect all the heterogeneous Network with the main more powerful central server on cloud and in this way in this Network name is HCRAN, for reducing the cost and load in this paper we properly study existing system and then some problems that present in the previous Network reduce or eliminate in this Network ,like overloading ,Energy consumption, reduced in this Network but Throughput increased and dead nodes decreases in this Network .In this thesis paper we increases the overall performance of the HCRAN by using the base station shifting technique and changes the method of devices connected with the base-station in the previous HCRAN the devices connect with the base station according to the distance but in this paper the distance and energy factor considered for connection for improving the performance of system ,in this way by implementing this techniques in the HCRAN the energy consumption and overloading, main problems in the previous HCRAN resolves in this system. The overall work divided in three scenario in the first scenario the base stations shifting technique that is new technique shows in simulations results and in the second scenario the connection process between the base- stations and devices in system shows according to distance and energy factor and in the third scenario the overall work combined and shows the wake up situations after sleep and connection with the nearest base- station shows in this thesis paper.